Implementasi Algoritma Searching Untuk Pencarian Produk dan SMTP Sistem Pengiriman Email pada Toko Ono Celluler - Dwityo Fauzan Nugroho; Wawan Gunawan (FORMAT, 2023)
Globalization makes all developments so fast, one of the factors that makes developments develop rapidly is technology. Technology was created to facilitate the work of everyone who needs it, one of them in large and small businesses. In the case of Ono Celluler Stores where they carry out several business activities using manual methods, these activities include recording sales, stock management, and employee management. Some of the activities currently implemented by Ono Celluler make doing business too long and ineffective. Apart from several problems that occur, Ono Celluler has a weakness in the introduction of Ono Celluler itself. This will affect what Ono Celluler is. The purpose of this research is to make an application that is able to solve problems that occur in Ono Celluler, this application will have a searching algorithm to make it easier for application users to find what products are available on Ono Celluler and features to help users. The Ono Celluler application will also have an information system to manage and monitor the products available at the Ono Celluler Store, besides that there will be a send mail feature to send formal emails from Ono Celluler. Research conducted using the waterfall method concluded that Ono Cellular's business processes can be carried out efficiently, difficulties in finding products are resolved properly using the searching algorithm. And employees can carry out business processes that are more organized and more formal using SMTP.